(3JWHjbGJ aj GdEYdGe GdQbejs - (3eMeO Tajb(B, (3gHIs; (3YHO GdQMef GdeUQj, EjgGH YjSis ((3eUQs (3ecJHI GdhaGA GdbGfhfjIs, 2023)
(3eaghe UMGaI GdHjGfGJ, eejRGJ GdEfahLQGajc, fTCI UMGaI GdHjGfGJ, echfGJ GdEfahLQGajc, CfhGY GdEfahLQGajc, eQGMd JUeje GdGfahLQGajc, ehGUaGJ UMaj GdHjGfGJ, eSJbHd UMGaI GdHjGfGJ, eaghe UMGaI GdehHGjd, UMGaI GdehHGjd heSJbHd GdUMGaI GdhQbjI, CgOGa UMGaI GdehHGjd hGSJNOGeGJgG, NUGFU UMGaI GdGdehHGjd, GdHQGeL hGdJWHjbGJ GdeSJNOeI aj GfJGL UMGaI GdehHGjd, NWhGJ GfJGL bUI NHQjI ef NdGd UMGaI GdehHGjd, fTCI UMGaI GdajOjh, eaghegG hegGQGJgG , GdajOjhLQGa, eSJbHd GdGYdGe GdQbej, hXGFa GdEYdGe GdQbej, CNdGbjGJ GdYed aj GdGYdGe GdQbej, JWhQ GdQSGdI GdEYdGfjI(B. s
Keywords: (3GdEYdGe GdQbejs; (3GdEYdGfs; (3GdJaGYd GdELJeGYjs; (3UMGaI GdHjGfGJs